Suizspacio. Transport Infrastructure as a Cultural Platform. Ñuñoa, Santiago de Chile, 2022. - Arturo Scheidegger; Ignacio García Partarrieu (ARQ, 2023)
Through a strategic intervention that connects six underground levels, Suizspacio demonstrates the potential to create public spaces within existing infrastructure, repurposing the remnant space of a metro station into a versatile and accessible cultural device.